ROLES AND FUNCTIONS OF TRANSFORMATIONAL LEADERSHIP IN IMPROVING THE PASKIBRA HIGH SCHOOL ORGANIZATION PERFORMANCE - Anam, Choirul; Thoyib, Armanu; Djawahir, Achmad Helmy (Universitas Brawijaya, Indonesia, 2018)
This study aims to reveal and give meaning to Transformational leadership based on perception by informants in paskibra(Flag hoisting troops) at High School.This study is a qualitative research with case study approach. This study was conducted on the paskibra SMA Laboratorium Universitas Negeri Malang (UM Laboratory School). Informants in this study amounted to ten informants who are in paskibra SMA Laboratorium UM. Data collection is done by interview, observation, and documentation. Data analysis includes data collection, data reduction, data presentation, interpretative data, and conclusion. The results show that the first proposition is individualized consideration formed by coaching, nurturing, respecting others, and organizational values. In the second proposition is idealized influence formed with confidence, commitment, loyalty, and professional. Next, the third proposition is intellectual stimulation formed by coordination, stimulation, fighting power, work ethic, and support. Furthermore, the fourth proposition is inspirational motivation formed with philosophy, ideas, motivation, vision and mission, and sharing. the fifth proposition of attributed charisma is formed by the soul of leadership, responsible, and communicative. the sixth proposition is that the Organizational Performance of paskibra is reflected by internal performance and external performance. Researchers also found in the process of the formation of components of Transformational leadership through education (learning and experience). Transformational leadership components of each individual or group have the ability to an organizational performance of paskibra can be implemented properly by members. This finding is related to one of the theories of education, namely experience learning and ability theory.